2009
DOI: 10.1111/j.1542-474x.2008.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Short QT Interval: A Novel Predictor of Androgen Abuse in Strength Trained Athletes

Abstract: To the best of our knowledge, there is no published report regarding electrocardiographic diagnosis and screening of AAS abusing athletes. In the present study, we present an easy and applicable method to screen and diagnose AAS abusing among professional bodybuilders. In the presence of QTc interval < or = 380 ms in a bodybuilder, one would predict AAS abusing with 83% sensitivity and 88% specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 16 publications
6
28
1
1
Order By: Relevance
“…The present results are in contrast to the study by Chung et al 23 that has found no effect of AAS on QTc interval and those of Stolt et al 21 and Bigi et al, 22 which found that athletes who were AAS users had significantly shorter QT intervals than AAS-free athletes. Bigi et al 22 examined only the QTc interval duration in 165 male professional bodybuilders and they found that those who subjected themselves to AAS abuse had a shorter QTc interval than AAS-free bodybuilders and healthy sedentary men.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…The present results are in contrast to the study by Chung et al 23 that has found no effect of AAS on QTc interval and those of Stolt et al 21 and Bigi et al, 22 which found that athletes who were AAS users had significantly shorter QT intervals than AAS-free athletes. Bigi et al 22 examined only the QTc interval duration in 165 male professional bodybuilders and they found that those who subjected themselves to AAS abuse had a shorter QTc interval than AAS-free bodybuilders and healthy sedentary men.…”
Section: Discussioncontrasting
confidence: 84%
“…Bigi et al 22 examined only the QTc interval duration in 165 male professional bodybuilders and they found that those who subjected themselves to AAS abuse had a shorter QTc interval than AAS-free bodybuilders and healthy sedentary men. Stolt et al,21 in contrast, evaluated 30 AAS-free endurance athletes, 15 power athletes who were AAS users and 15 AAS-free sedentary men, and found that endurance athletes with physiological adaptive left ventricular hypertrophy had prolonged QT duration, but their QT dispersion was similar to that of sedentary men.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, in these studies, only QTd and cQTd were used to access homogeneity of cardiac repolarization, and no information about the relation between transmural dispersion of repolarization and long-term AAS using athletes. 40,41 Transmural dispersion of repolarization, calculated as the interval between the peak and the end of T wave on electrocardiogram, has been related to ventricular arrhythmias and sudden cardiac death. 18,19,35 Recent studies indicated that Tp-e interval, Tp-e/QT ratio, and Tp-e/cQT ratio can be used as an index of total (transmural, apicobasal, and global) dispersion of repolarization.…”
Section: Discussionmentioning
confidence: 99%